Co2 exchange and biomass development of the herbaceous vegetation in the portuguese montado ecosystem during spring - Hussain, M.Z. (2009)
Montado are spatially heterogeneous ecosystems that are economically important for the production of cork and herbaceous biomass that provide fodder for animals. Understanding of how trees and the herbaceous layer interact to determine pasture yield and the overall CO2 exchange of the herbaceous layer is crucial. Portable chamberswere used to study CO2 exchange by the herbaceous layer component of the montado ecosystem in southern Portugal. Biomass, Net herbaceous layer CO2 exchange (NEE) and respiration (Reco) were measured in the open and understory locations between March and May, during the active growing period. Parameter fits on the NEE data were performed using empirical hyperbolic light response model, while ecosystem respiration (Reco) data were fitted with a two-parameter exponential model. Annual green biomass productions were 405.8 9.0 and 250.6 6.3 g m 2 in the open and the understory, respectively. The respective maximum NEE during the day were 24.0 2.9 and 9.6 2.2 mmol m 2 s 1 while maximum Reco were 20.6 2.2 and 10.0 1.6 mmol m 2 s 1, occurring in April. Photosynthetic photon flux density (PPFD) explained more that 70% of variations in daytime NEE while soil temperature at 10 cm depth (Tsoil) explained >50% of the variations in Reco under non-limiting soil moisture conditions. Both the herbaceous layer communities shared similar plant functional types and no significant difference in nutrient nitrogen (N) occurred between them. The two herbaceous layer components shared similar physiological characteristics and differences that arose in their CO2 uptake capacities and green biomass production were the result of microclimatic differences created by tree shading